Influence of Low Inlet Pressure and Temperature on the Compressor Map Limits of Electrical Turbo Chargers for Airborne Fuel Cell Applications - Jonas Schröter; Daniel Frank; Valentin Radke; Christiane Bauer; Josef Kallo; Caroline Willich (Energies, 2022)
For the optimal high-efficiency operation of a PEM fuel cell system, the temperature, pressure, humidity and mass flow of the supplied air must be tuned to the fuel cell stack requirements. Especially for aircraft applications, this requires a thorough understanding of the fuel cell air supply system behavior and how it changes when the ambient pressure is below 1 bar(a) during flight. This work investigates the influence of low inlet pressures and varying inlet temperatures on the compression map of an electrical turbo charger. This is especially relevant in airborne fuel cell application and not much literature can be found on that topic. Compressor limits are evaluated experimentally and theoretically. The theory of mass flow and speed correction is compared to experimental findings and found to be applicable for the surge and speed limit of the investigated turbo chargers as long as the compressor map is not limited by the power of the electric motor and inverter. Based on this, a prediction of the compressor map for altitudes up to 10,000 m is made with the help of a developed software tool.